صعوبات تطبيق معايير الاعتماد الأكاديمي في جامعة تشرين من وجهة نظر أعضاء الهيئة التعليمية (دراسة حالة) - طويل علاء (Latakia University Journal -Medical Sciences Series, 2016)
يعتبر تطبيق معايير الجودة والاعتماد الأكاديمي أمراً مهماً في مسيرة التعليم العالي، لما له دور في تحقيق الجودة والتميز والوصول إلى المستويات العالمية من خلال وضع معايير عامة لتقييم فعالية التعليم الجامعي. لذلك هدف البحث إلى التعرف على الصعوبات التي تعيق تطبيق معايير الاعتماد الأكاديمي (المعتمدة من قبل مجلس اتحاد الجامعات العربية، والتي وزعت على عدة محاور هي: رؤية ورسالة وأهداف المؤسسة، والقيادة والتنظيم الإداري، والموارد، وشؤون الطلاب، والخدمات الطلابية، وخدمة المجتمع، وأعضاء الهيئة التدريسية، والبرامج الأكاديمية، وطرائق التدريس ومصادر التعلم، والكتاب الجامعي، والبحث العلمي، والتقويم، والأخلاقيات الجامعية) في التعليم العالي من وجهة نظر أعضاء الهيئة التعليمية في جامعة تشرين. واشتملت عينة البحث على (431) عضو هيئة تعليمية من مختلف كليات والمعاهد العليا في جامعة تشرين. ولتحقق هدف البحث صممت استبانة احتوت على (59) فقرة موزعة على (7) محاور هي (أعضاء الهيئة التدريسية، والبرامج الأكاديمية، وطرائق التدريس ومصادر التعلم، والكتاب الجامعي، والبحث العلمي، والتقويم، والأخلاقيات الجامعية). وقد أظهرت النتائج أن أهم الصعوبات على مستوى محور أعضاء الهيئة التدريسية كانت: غياب البرامج التدريبية لتطوير مهارات أعضاء الهيئة التدريسية، وغياب المكافآت التشجيعية للمبدعين في مجال التدريس والبحث العلمي المتميز؛ محور البرامج الأكاديمية: عدم توفر الكتيبات والأدلة اللازمة التي تعرض بوضوح اللوائح التي تحكم البرامج التعليمية وإجراءات القبول والانسحاب، وغياب استيضاح مدى ملائمة البرامج لاحتياجات المجتمع وسوق العمل ومتطلبات التنمية المعرفية؛ محور طرائق التدريس ومصادر التعلم: : غياب التدريب المناسب لتنمية وتطوير مهارات وقدرات أعضاء هيئة التدريس على استخدام طرائق التدريس ومصادر التعلم، وغياب الأبحاث التقويمية عن الطرائق المستخدمة في تدريس الطلبة؛ محور الكتاب الجامعي: غياب التصميم الجيد للكتاب الجامعي من حيث الشكل، الطباعة، الورق، الرسوم والأشكال وغيرها، وكذلك عدم تأكد المؤسسة من صحة ودقة وحداثة محتوى الكتاب الجامعي؛ محور البحث العلمي: عدم توفير الفرص لمساهمة أعضاء هيئة التدريس في المؤتمرات والندوات العلمية وورش العمل العلمية. وعدم توفر بيئة داعمة للبحث والنشر والتطوير؛ محور التقويم: غياب الآلية لتقويم الخريجين ومدى نجاحهم في مجالات العمل بعد التخرج، وعدم اعتماد المؤسسة على الدراسات التقويمية لتحديد وتحليل المشكلات التي تعوق تنفيذ البرنامج واقتراح الحلول؛ محور الأخلاقيات الجامعية: غياب نظاما يكفل تكافؤ الفرص والعدالة في التعيين أو الاختبار أو المنح أو الحوافز، غياب الشفافية في التعاملات الإدارية والمالية في المؤسسة. The Application of Academic Accreditation Standards is very important in the context of higher education, for its role in achieving quality and outstanding to reach the international levels through setting general standards to evaluate university education efficiency. Therefore, the research aimed to identify the difficulties that hinder the application of academic accreditation standards ( adopted by Arab Universities Union Board, which consist of several axels: vision- mission and goals of the institution, leadership and managerial organization, resource, students affairs, students services, community services, teaching staff, academic programs, teaching methods and learning resources, study books, scientific research, evaluation and university morals ) at higher education from the teaching staff members’ view point at Tishreen University. The research sample included (431) teaching staff members from different faculties and higher institutes at Tishreen University. For this research goal, a questionnaire was set down to include (59) items distributed on (7) axles: teaching staff members, academic programs, teaching methods and learning sources, university books, academic research, evaluation and university morals. The results showed serious difficulties on the level of teaching staff members axle: lack of training programs to develop teaching staff members skills, as well as, the lack of encouraging awards for creators in the domain of distinguished academic research. Also, for academic programs axle: lack of necessary guide notebooks that show clearly regulations which control teaching programs, admission procedures and leakage , in addition to the ambiguity of program convenience to the needs of the community, labor market and knowledge raising. Meanwhile, for teaching methods and learning sources axle: no suitable training to raise and develop skills and capabilities of teaching staff members to use teaching methods and learning sources and the lack of evaluative researches concerning the methods used in teaching students Moreover, for the university books axle: no good designs for the university books , in terms of form, printing, quality of paper, figures and drawings, as the institute is not aware of the accuracy, modernity and right of the books. And for academic research: no opportunities for teaching staff members for contribution to academic conferences, forums and workshops, as well as, there is no supporting environment for development, publishing and research. Besides, for evaluation axle: no mechanism to evaluate the alumni and their success in the labor market after graduation, as the institute does not depend on evaluation studies to identify and analyze problems that hinder program activation and suggesting solutions. Finally, for the university ethics: no system to maintain equity and justice at employments, tests, grants or incentives, in addition to the absence of transparency at financial and paper work procedures at the institute.